WCN24-2649 Calcified masses in a peritoneal dialysis patient: uremic tumor calcinosis - Cueva Chuquihuanca, Claudia Alexandra (2024)
Uremic tumor calcinosis is an uncommon condition characterized by calcium salt deposition in different regions of periarticular soft tissue in patients with chronic kidney disease. Its prevalence is estimated at 1.6% in patients receiving peritoneal dialysis. The risk factors described for the development of this pathology include persistent hyperphosphatemia, elevated levels of calcium x phosphorus (CaxP) product, and severe secondary hyperparathyroidism. Diagnosis is based on the clinical presentation of masses in periarticular areas, laboratory tests related to alterations in bone and mineral metabolism (calcium, phosphorus, parathormone), imaging of the lesion, and, if possible, a biopsy of the lesion. This case is particularly interesting because the diagnosis of uremic tumor calcinosis is based on histopathological findings and existing clinical correlation.